Unusual fatigue and failure to utilize EMS are associated with prolonged prehospital delay for suspected acute coronary syndrome - DeVon, Holli A. (Crit Pathw Cardiol, 2020)
Rapid reperfusion reduces infarct size and mortality for acute coronary syndrome (ACS), but efficacy is time dependent. The aim of this study was to determine if transportation factors and clinical presentation predicted prehospital delay for suspected ACS, stratified by final diagnosis (ACS vs. no ACS). A heterogeneous sample of emergency department (ED) patients with symptoms suggestive of ACS were enrolled at five U.S. sites. Accelerated failure time models were used to specify a direct relationship between delay time and variables to predict prehospital delay by final diagnosis. Enrolled were 609 (62.5%) men and 366 (37.5%) women, predominantly Caucasian (69.1%), with a mean age of 60.32 (±14.07) years. Median delay time was 6.68 (CI 1.91, 24.94) hours; only 26.2% had a prehospital delay of 2 hours or less. Patients presenting with unusual fatigue (TR=1.71, p=0.002; TR=1.54, p=0.003, respectively) or self-transporting to the ED experienced significantly longer prehospital delay (TR 1.93, p<0.001; TR 1.71, p<0.001, respectively). Predictors of shorter delay in patients with ACS were shoulder pain and lightheadedness (TR=0.65, p=0.013 and TR=0.67, p=0.022, respectively). Predictors of shorter delay for patients ruled out for ACS were chest pain and sweating (TR=0.071, p=0.025 and TR=0.073, p=0.032, respectively). Patients self-transporting to the ED had prolonged prehospital delays. Encouraging the use of EMS is important for patients with possible ACS symptoms. Calling 911 can be positively framed to at-risk patients and the community as having advanced care come to them since EMS capabilities include 12-lead ECG acquisition and possibly high sensitivity troponin assays.